Perfil Profesional y Ocupacional del Ingeniero Químico (2018)
This project is developed with the objective of building the professional and occupational profile of the chemical engineer based on the graduates of the University of America in the years 2013, 2014 and 2015; It begins with a bibliographical consultation where a list of generic and specific competences is selected, the contextualization of each of them is carried out according to the current state of the country that accompanies the knowledge and skills that the professional must possess throughout his or her learning and based on this, a survey is constructed with the objective of evaluating the selected skills. The proper distribution of the survey is done to collect the data, from this some considerations are taken into account when approaching the design of the training profile. Initially, we want to establish a type of learning that consists of supplying the student with knowledge that allows understand how the different fields of description and scale in chemical engineering work together and how they relate to each other based on tools such as self-criticism and reflective action. This means that the professional must understand the basis of each process in the workplace, as such reason the profile is defined in four (4) parts, the first will be the nature of the profession where the meaning of chemical engineering is expressed; Second, the profile of the applicant is established, indicating the competences that this must possess for the development of knowledge in the field of chemical engineering, the third the profile of the graduate and finally the occupational profile.